2015
DOI: 10.1074/jbc.m114.628297
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Mer Tyrosine Kinase (MerTK) from the Cell Surface Contributes to the Regulation of Retinal Phagocytosis

Abstract: Background:The MerTK receptor is necessary for retinal phagocytosis and its daily rhythm. Results: MerTK is cleaved from the apical cell surface in vitro and in vivo, reducing the phagocytic capacity of RPE cells. Conclusion: MerTK cleavage might help control the duration of the daily phagocytic peak. Significance: Our data show that extracellular cleavage of MerTK partly regulates retinal phagocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 50 publications
2
53
0
Order By: Relevance
“…Phagocytosis of POS involves engagement of the actin–myosin cytoskeleton via the Mer/TK signalling complex whose activation controls the binding of POS to the RPE surface (Law et al ., 2015) under the control of a recently reported regulatory gene, Klotho (Kokkinaki et al ., 2013), while signalling via MerTK/Axl/Gas6 is required for phagocytosis of apoptotic cells in macrophages (Zagorska et al ., 2014). However, the process of cytokinesis depends on much more extensive changes to the actomyosin/tubulin cytoarchitecture involving inhibition of centrosome polarization (Schiebel, 2000), and indeed, the close relationship between mutlinucleation and cytokinesis was confirmed in the present work where treatment with blebbistatin prevented cytokinesis in nearly 50% ARPE19 cells, and many cells became multinucleated.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis of POS involves engagement of the actin–myosin cytoskeleton via the Mer/TK signalling complex whose activation controls the binding of POS to the RPE surface (Law et al ., 2015) under the control of a recently reported regulatory gene, Klotho (Kokkinaki et al ., 2013), while signalling via MerTK/Axl/Gas6 is required for phagocytosis of apoptotic cells in macrophages (Zagorska et al ., 2014). However, the process of cytokinesis depends on much more extensive changes to the actomyosin/tubulin cytoarchitecture involving inhibition of centrosome polarization (Schiebel, 2000), and indeed, the close relationship between mutlinucleation and cytokinesis was confirmed in the present work where treatment with blebbistatin prevented cytokinesis in nearly 50% ARPE19 cells, and many cells became multinucleated.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that RPE cells share similar clearance mechanisms to those used by other phagocytes (e.g., macrophages and dendritic cells) to phagocytose shedded POS [3] . Previous studies have shown that certain receptors on RPE cells, such as common phagocyte receptor (TAM receptor tyrosine kinase Mer) [26][27][28] , scavenger receptor (CD36) [29] , and the integrin adhesion receptor (ανβ5) [30] , are involved in the phagocytosis of shedded POS. However, little is known about the involvement of opsonization-mediated phagocytosis (a well-known mechanism in macrophages) in RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the kinase domain contains three autophosphorylation sites (Tyr‐749, Tyr‐753, Tyr‐754), which are critical for its full activity (Ling, Templeton, & Kung, ). MERTK exists as a membrane‐bound receptor and as a soluble form (Sather et al., ) through its cleavage at proline 485 by ADAM17 (MIM# 603639), at least in murine macrophages and RPE cells (Law et al, ; Thorp et al., ). This soluble form would act as a negative feedback loop limiting POS binding to RPE cell surface prior to phagocytosis (Nandrot et al, ).…”
Section: Introductionmentioning
confidence: 99%